Child Stunting in Southeast Asia and Indonesia: A Disregard for the Right to Survival and Development? - Hafandi, Raisha (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2024)
The objective of this research paper is to examine and clarify the regulations and policies that pertain to the application of the fundamental notion of the right to development for children. In addition to the aforementioned, an investigation will be conducted into the measures taken by the Association of Southeast Asian Nations (ASEAN) and Indonesia to address the prevalence of stunting in the region. There is a greater prevalence of stunted children in countries situated primarily in South and Southeast Asia, as well as in countries in sub-Saharan Africa. Indonesia is among the countries with a high occurrence of undernourishment, including stunting. Stunting in Indonesia represents a substantial public health concern that necessitates a multi-faceted and collaborative approach. The issue of stunting can impinge upon the state’s obligation to fulfil the rights to survival and development in children. In essence, the United Nations Committee on the Rights of the Child has interpreted the concept of child development as requiring an understanding that extends beyond the physical to encompass mental, moral, spiritual and psychological dimensions. The research is supported by data drawn from two sources: doctrinal data and data derived from empirical observation. However, empirical data is obtained from the results of previous research, which were derived from observations conducted in the field. It can therefore be concluded that stunting represents a concrete violation of the rights of the child to survival and development. In response, the ASEAN and Indonesia have enacted a series of policies and regulations aimed at addressing the issue of stunting in Southeast Asia and Indonesia. Furthermore, it is essential to implement a multisectoral approach to stunting reduction in Indonesia that engages health workers, families, the government, and communities.Keywords: Stunting, Children Rights, Development.